2002
DOI: 10.1152/jn.00624.2001
|View full text |Cite
|
Sign up to set email alerts
|

Sodium Channel Blocking Actions of the κ-Opioid Receptor Agonist U50,488 Contribute to Its Visceral Antinociceptive Effects

Abstract: . Sodium channel blocking actions of the -opioid receptor agonist U50,488 contribute to its visceral antinociceptive effects. J Neurophysiol 87: 1271-1279, 2002; 10.1152/jn.00624.2001. The goal of the present study was to determine whether the -opioid receptor agonist (ORA) U50,488 attenuates behavioral and primary afferent nerve responses to noxious colorectal distension (CRD) by sodium channel blockade. We tested the analgesic -ORA (Ϯ)-trans U50,488, its enantiomers (Ϫ)-trans (1S,2S)-U50,488 and non -ORA (ϩ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

2
47
1

Year Published

2003
2003
2015
2015

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 65 publications
(50 citation statements)
references
References 29 publications
2
47
1
Order By: Relevance
“…This hypothesis was directly addressed by investigating the effects of (Ϫ)-(1S,2S)-U50,488 and (ϩ)-(1R,2R)-U50,488 on voltage-gated sodium currents in colon sensory neurons in the S1 dorsal root ganglion. Both U50,488 enantiomers decreased voltage-gated sodium currents with comparable potencies even in the presence of opioid receptor antagonism (Su et al, 2002). Such findings demonstrate that the two U50,488 enantiomers have comparable potency in blocking voltage-gated sodium channels, but drastically different actions on the KOR.…”
mentioning
confidence: 64%
See 4 more Smart Citations
“…This hypothesis was directly addressed by investigating the effects of (Ϫ)-(1S,2S)-U50,488 and (ϩ)-(1R,2R)-U50,488 on voltage-gated sodium currents in colon sensory neurons in the S1 dorsal root ganglion. Both U50,488 enantiomers decreased voltage-gated sodium currents with comparable potencies even in the presence of opioid receptor antagonism (Su et al, 2002). Such findings demonstrate that the two U50,488 enantiomers have comparable potency in blocking voltage-gated sodium channels, but drastically different actions on the KOR.…”
mentioning
confidence: 64%
“…Subsequent electrophysiological studies confirmed that this nonopioid effect of U50,488 was due to a direct blockade of voltage-gated sodium channels in cardiac myocytes (Pugsley et al, 1993(Pugsley et al, , 1994. The sodium channel blocking actions of -ORAs have been replicated in hippocampal CA3 neurons (Alzheimer and Bruggencate, 1990), neuroblastoma cells (Zhu and Im, 1992) and more recently in primary sensory neurons in the dorsal root ganglion (Su et al, 2002). Another line of evidence for opioid receptor-independent blockade of sodium channels by -ORAs such as U50,488 derives from experiments using heterogeneous expression of sodium channels in oocytes (Pugsley et al, 2000).…”
mentioning
confidence: 89%
See 3 more Smart Citations